2020
DOI: 10.3390/geosciences10110446
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Geophysical Mapping and Hydrogeological Characterisation of the Subsurface for Optimal Placement of Infiltration-Based Sustainable Urban Drainage Systems

Abstract: The continuous growth of cities in combination with future climate changes present urban planners with significant challenges, as traditional urban sewer systems are typically designed for the present climate. An easy and economically feasible way to mitigate this is to introduce a Sustainable Urban Drainage System (SUDS) in the urban area. However, the lack of knowledge about the geological and hydrogeological setting hampers the use of SUDS. In this study, 1315 ha of high-density electromagnetic (DUALEM-421S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 46 publications
0
4
0
2
Order By: Relevance
“…Soil texture and structure relate to infiltration and percolation which contribute to groundwater recharging. Previous studies have shown relatively higher percolation in sand-dominated units than clay units (Andersen, 2020). In addition, compacted sediment, which limits the pores, affects infiltration ability.…”
Section: Lithology Impactmentioning
confidence: 90%
“…Soil texture and structure relate to infiltration and percolation which contribute to groundwater recharging. Previous studies have shown relatively higher percolation in sand-dominated units than clay units (Andersen, 2020). In addition, compacted sediment, which limits the pores, affects infiltration ability.…”
Section: Lithology Impactmentioning
confidence: 90%
“…Urbanized areas have been increasing in developing countries, mainly due to population growth; population migration from smaller to larger urbanized areas; regional displacements due to social and economic conditions; and, within an urbanized area, displacement from more central to peripheral areas [1,2]. This increase in urbanized areas has led to the occupation of areas with very distinct environmental characteristics, from aquifer recharge areas to areas subject to hazardous events with different natural, quasi-natural, natural-technological, and anthropogenic sources [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Several procedures have been proposed to alter the partitioning between surface runoff and infiltration, with an emphasis on sustainable drainage systems (SuDSs) used in urban environments, roadworks, and special-use areas such as industrial parks. SuDSs have been developed since the 1990s, with a set of techniques and measures that can be adopted depending on the land use characteristics and, especially, on the environmental components, as shown by [1,2,[8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Com o objetivo de alterar a proporção entre o escoamento superficial e a infiltração, diversos procedimentos têm sido propostos com ênfase aos Sistemas de Drenagem Sustentáveis (SDSs) que tem seu desenvolvimento a partir dos anos 1990 com diversos trabalhos em diferentes países, principalmente, na Inglaterra (Butler & Parkinson, 1997;CIRIA 2000aCIRIA , 2000bCIRIA , 2006; Dearden & Price 2011, 2012Dearden et al, 2013;Zhou, 2014). A adoção desses sistemas e suas instalações dependem de um grupo de características dos componentes do meio ambiente que interferem e, mesmo, inviabilizam a adoção dessas alternativas que visam minimizar os problemas gerados pelo aumento do escoamento superficial e, assim controlem os problemas decorrentes das mudanças geradas pela urbanização.…”
Section: Introductionunclassified